Synthesis and Biocompatibility Studies of New Iminodiacetic Acid Derivatives - Magdalena Markowicz-Piasecka; Piotr Dębski; Elżbieta Mikiciuk-Olasik; Joanna Sikora (Molecules, 2017)
Background: Iminodiacetic acid (IDA) derivatives can be used as ligands to form complexes with technetium, with potential application as hepatobiliary diagnostic agents. The aim of this study was to synthesize five novel IDA derivatives and to compare their effects on plasma haemostasis with clinically approved ligands for technetium complexation. Methods: The influence of synthesized IDA derivatives on plasma haemostasis was evaluated spectrophotometrically by clot formation and lysis test (CL-test), coagulation assay, Prothrombin Time and Activated Partial Tromboplastin Time. The effects of the tested compounds on erythrocytes were assessed using haemolysis assays, microscopy and flow cytometry studies. Results: Despite their significant influence on the kinetic parameters of the process of clot formation and fibrinolysis, the tested ligands, at potential diagnostic concentrations, did not alter the overall potential of clot formation and lysis (CLAUC). At potential diagnostic concentrations (0.4 μmol/mL) all the tested compounds showed no adverse effects on the membranes of RBCs (Red Blood Cells). Conclusion: IDA derivatives with methoxy substituents in aromatic ring, exert multidirectional effects on plasma haemostasis and should be considered safe as their significant impacts were mostly observed at 4 μmol/mL, which is about 10-fold higher than the theoretical plasma concentrations of these compounds.